0032 Absence Of Nlrp3 Inflammasomes Reduces Cognitive Performance Impairments Induced By Sleep Loss. (27th April 2018) - Gerashchenko, D; Niznikiewicz, M M; Johnston, A M; Basheer, R; Strecker, R E; Zielinski, M R
Abstract: Introduction: The NLRP3 (nucleotide-binding domain leucine rich family pyrin containing 3) inflammasome is a protein complex that activates the somnogenic pro-inflammatory cytokines interleukin (IL)-1beta and IL-18. The NLRP3 inflammasome is enhanced in the somatosensory cortex after sleep deprivation. However, the role of NLRP3 inflammasomes effect cognition after sleep loss is unknown. Methods: Two-month old NLRP3 knockout (KO) and wild-type (WT) mice were sleep deprived for 6 h or allowed to sleep ad libitum (baseline). Mice were subjected to the novel object recognition test and the cortically dependent floor texture recognition test. Additional mice were perfused and brains were collected and processed for immunohistochemistry, or prefrontal cortex and hippocampus were dissected, flash frozen and processed for gene expression analysis. Tissues were double-labeled with anti-IL-18 and anti-IL-1beta, anti-NLRP3, and anti-NeuN (neuronal) or anti-CD11b (microglia) and quantified. NLRP3, ASC, IL-1beta, IL-18 mRNA expression was analyzed by real-time polymerase chain reaction. Results: Sleep deprivation reduced the time exploring the novel object (indicator of impaired cognition that is partially hippocampal dependent) in WT mice (p=0.008) but not NLRP3 KO mice. Similarly, sleep deprivation significantly reduced the time exploring the textured floor (indicator of impaired cortical-dependent cognition) in WT (p=0.049) but not NLRP3 KO mice. The expression of inflammasome components NLRP3 and ASC and IL-1beta and IL-18 were enhanced in the frontal cortex and hippocampus (p<0.05 for all) after sleep deprivation in WT but not NLRP3 KO mice. A similar pattern of inflammasome and cytokine activation occurred in neurons and microglia within the frontal cortex and hippocampus of WT mice ( 30% enhancement or greater) after sleep deprivation but was absent in the KO mice. Conclusion: These results indicate that NLRP3 inflammasomes and associated inflammatory cytokines are enhanced in the frontal cortex and hippocampus after sleep loss and are critical for cognitive detriments induced by sleep loss. Support (If Any): Veterans Affairs I01RX00928 (MRZ), I01BX001404 (RB), I01BX002774 (RES)